Variabilidade e herança da resistência de mangueira (Mangifera indica L.) aos fungos Lasiodiplodia theobromae e Neofusicoccum parvum - Coelho, Washington Carvalho Pacheco (2018)
The fungi Lasiodiplodia theobromae and Neofusicoccum parvum are pathogens responsible for reducing mango yield due to dieback, which both cause in the culture. Inheritance studies and variability in accessions for fungal diseases in mango, in general, are quite limited, despite their importance for the development of cultivars. The goals of this study were1) to evaluate the inheritance of resistance to dieback disease caused by L. theobromae and N. parvumin three crossings, and 2) evaluate 75mango accessions for resistance to these fungi to support mango breeding programs. Young branches containing young leaves were selected, and suspension of 103 conidia/mL of L. theobromae or N. parvum was sprayed, separately. After inoculation, leaves were protected in a plastic wet chamber for 48 hours. The infection was estimated by taking the branches without symptoms/total number of inoculated branches. Plants without disease symptoms in more than 90% of the brancheswere considered as resistant. Monogenic resistance, conferred by recessive alleles, was observed for L. theobromae for the three crossings evaluated, despite the 13:3 segregation detected for 'Keitt' x 'Tommy Atkins'. For N. parvum, recessive resistance with 3:1 monogenic segregation was observed in the crossing 'Keitt' x 'Tommy Atkins', and 9:7 epistatic segregation was observed in the crossing ‘Haden’ x ‘Tommy Atkins’ and ‘Espada x ‘Tommy Atkins’. ‘Apple DCG’, ‘Ataulfo’, ‘Da porta’, ‘Dashehari’, ‘Espada’, ‘Haden’, ‘Haden 2H’, ‘Heidi’, ‘Irwin’, ‘Keitt’, ‘Kent’, ‘Néldica’, ‘Recife’ and ‘Smith’ were resistant to both pathogens, being promising for breeding programs. 'Rosa' are resistant to L. theobromae, and susceptible to N. parvum. 'Tommy Atkins', the most grown cultivar in the São Francisco valley, was susceptible to both pathogens.The mono or digenic inheritance observed in the present study indicates the possibility of selection in the F2 generation and identification of plants with double resistance to L. theobromae and N. parvum in mango trees.